Penerapan Metode Mustaqilli Pada Mata Pelajaran Bahasa Arab di MTsPN 4 Medan - Umayya, Nur Abidah (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research was carried out with the aim of finding out the application of the Mustaqilli method in Arabic language subjects at MTsPN 4 Medan for class VII middle school students and to find out the planning, implementation and evaluation of the application of the Mustaqilli method in Arabic language subjects. This research uses descriptive qualitative research which tends to use analysis. The data collection techniques in this research are observation, interviews and documentation. The application of the mustaqilli method is a method that takes a comprehensive approach by mastering the techniques of reading books, writingtranslating, composing until being able to speak Arabic. The obstacle in implementing the mustaqilli method is that students have different backgrounds and abilities in learning Arabic. The results of this research show that the mustaqilli method can improve students' understanding of Arabic language lessons.